HR Challenges in the Indian BPO Industry A Qualitative Study - Koshy, Shiju Rajan (2005)
This study uncovers the challenges faced by multinational call centres in India. Managers of three calls centres were interviewed to understand the challenges faced by them. Emphasis is placed on the four HR functions namely staffing, training and development, motivation and maintenance.From the analysis four key lessons are suggested i.e. 1) actively manage the challenges of hyper-growth of a new industry within the context of an emerging economy, 2) make decisions based on factors beyond wage differentials, 3) provide clearly defined career opportunities for employees and 4) leverage the global corporate reputation and local experience